Treatment Study of Ruqyah Syirkiyyah towards Witchcraft (Cultural Anthropology Study) in Bandar Setia Village, Percut Sei Tuan Sub-district, Deli Serdang District - Muhammad Fadli; Khairani Khairani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This study aims to find out and describe the treatment practice of Ruq'yah Syirkiyyah towards witchcraft in Bandar Setia Village, Percut Sei Tuan Sub-district, Deli Serdang District. This study is qualitative research with an ethnographic approach. The techniques of collecting data are in-depth observations and interviews. The informants in the study are two people as experts in treatment and seven witnesses and patients. Based on the results of the study obtained in the field that the treatment of ruqyah syikiyyah is a treatment that combines the verses of the Qur'an, and local beliefs in the treatment practice towards witchcraft. The method used in the treatment is the four-point concept of nature as a media caller khodam with dhikr, seven mosques water, ape tiger flowers, and Minya bunibawasa to revoke magical objects that exist on the patient's body and in the process of healing, the patient must perform another special ritual such as feeding orphans and making a salvation event as a symbol of gratitude by the patient's family. The conclusion is that the treatment of ruqyah shirkiyyah is a religious treatment that mixes the local belief system, and in performing the treatment of witchcraft that is doing the dreamy stage, pull out magical objects, and the patient's family performs a ritual of salvation as a symbol of gratitude.